2014
DOI: 10.1186/1746-6148-10-135
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance aerial dispersal modelling of Culicoides biting midges: case studies of incursions into Australia

Abstract: BackgroundPrevious studies investigating long-distance, wind-borne dispersal of Culicoides have utilised outbreaks of clinical disease (passive surveillance) to assess the relationship between incursion and dispersal event. In this study, species of exotic Culicoides and isolates of novel bluetongue viruses, collected as part of an active arbovirus surveillance program, were used for the first time to assess dispersal into an endemic region.ResultsA plausible dispersal event was determined for five of the six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 31 publications
4
56
0
Order By: Relevance
“…Eight of 10 genome segments of BTV_2_AUS_2008 are most closely related to the cognate segments of viruses from Taiwan and Asia and not other Australian BTVs, supporting the conclusion that the virus entered Australia recently (14). Since live ruminants are not imported, BTV vaccines are not permitted, and Australia is separated from Asia by water, the movement of BTVs into Australia is believed to be by way of wind-borne dispersal of infected Culicoides (15)(16)(17).…”
mentioning
confidence: 79%
“…Eight of 10 genome segments of BTV_2_AUS_2008 are most closely related to the cognate segments of viruses from Taiwan and Asia and not other Australian BTVs, supporting the conclusion that the virus entered Australia recently (14). Since live ruminants are not imported, BTV vaccines are not permitted, and Australia is separated from Asia by water, the movement of BTVs into Australia is believed to be by way of wind-borne dispersal of infected Culicoides (15)(16)(17).…”
mentioning
confidence: 79%
“…Orthotrichia veikaba was recorded previously from 6 specimens collected at Veikabu, in the Central Province of Papua New Guinea. Both Torres Strait islands from which it is recorded here are situated very close to New Guinea and, given the dearth of permanent fresh water on these islands (Burrows & Perna 2009;Burrows 2010), and the fact that it has not been picked up on mainland Australia, it seems reasonable to consider this species to be a native New Guinea species, probably vagrant on the islands. Remarks.…”
Section: Microcaddisflies Of Australia's Northmentioning
confidence: 99%
“…Several artificial waterbodies near the island village contain permanent water year round, though of brackish quality.' Earlier, Burrows and Perna (2009) reported that on Saibai '[f]reshwater habitats … appeared limited to just the two small artificial water reservoirs located side by side'; otherwise, other than mangroves, they noted only '… brackish water wetlands.' Of Badu Island, Waltham et al (2014) reported '… more obvious freshwater habitats,' and illustrated their report with a photograph of a substantial water hole.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wind-spread models have been developed to model such dispersions and may be used to identify areas at risk of arboviral incursion due to windborne insects (65,66,67). Some models have been validated using field data and have proved useful in explaining the origins of incursions (67,68), demonstrating their potential value in informing surveillance programmes.…”
Section: Participatory Surveillancementioning
confidence: 99%